PERTUMBUHAN EKONOMI, SEKTOR UNGGULAN DAN KESENJANGAN PADA EMPAT KABUPATEN DI PULAU MADURA - Susanto, Dedi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2011)
The objective of this research was to know economic growth levels, economy patterns, supreme and non-supreme sectors and gaps on each regencies in Madura Island. This research used descriptive quantitative method. According to the analysis? results which had been conducted, it could be concluded that each regencies in Madura Island during the time period 2005 to 2009 the economic growth experienced fluctuation and the pattern of the economy had to be concerned in Sampang regency due to it fell in the relatively left behind criteria. While, for the supreme sectors, they needed to be more improved so that it would be more advanced. The gaps on these four regencies included in medium criteria, yet, the index value needed to be concerned because it tend to keep increase every year.